Development of an Optimized Drying Process for the Recovery of Bioactive Compounds from the Autumn Fruits of Berberis vulgaris L. and Crataegus monogyna Jacq. - Cadmiel Moldovan; Oleg Frumuzachi; Mihai Babotă; Luigi Menghini; Stefania Cesa; Alexandru Gavan; Cristian R. Sisea; Corneliu Tanase; Maria Inês Dias; Carla Pereira; Isabel C.F.R. Ferreira; Gianina Crișan; et al. (MDPI AG, 2021)
Hot air drying has proven to be an efficient method to preserve specific edible plant materials with medicinal properties. This is a process involving chemical, physical, and biological changes in plant matrices. Understanding these processes will lead to an improvement in the yields of bioactive compounds. This study aims to optimize the drying process of two species' fruits used in folk medicine, Berberis vulgaris and Crataegus monogyna. The optimized extracts' antioxidant capacity was assessed using various assays, with the barberry extract showing very good activity (50.85, 30.98, and 302.45 mg TE/g dw for DPPH, TEAC, and FRAP assays, respectively). Both species exerted good fungal α-glucosidase inhibitory activity (IC50 = 0.34 and 0.56 mg/mL, respectively) but no activity on mammalian α-glucosidase. Additionally, this study identified and quantified the main bioactive compounds. The results presented herein are a breakthrough in industrializing this drying process. Additional studies are necessary to mechanistically understand the drying process involved in these plant materials.